Gambaran fungsi paru pengrajin kayu di Desa Petulu Gianyar, Bali-Indonesia Asshiddiqie Chirac Sepakat Purba1, Luh Made Indah Sri Handari Adiputra2, I Made Muliarta2 - Asshiddiqie Chirac Sepakat Purba; Luh Made Indah Sri Handari Adiputra; I Made Muliarta (DiscoverSys Inc., 2019)
Introduction: The woodworking industry is experiencing very rapid growth. Petulu Village is a village famous for its wood crafts. The working environment in Petulu village has risk factors in the form of physical factors (dust, noise, heat, lighting), chemical factors, and the most important is Dust. The purpose of this study was to describe the description of lung function of wood craftsmen including (Gender, Age, Nutritional Status, Working Period, Smoking History and Use of Personal Protective Equipment) in Petulu Village, Gianyar, Bali.Method: This study is a descriptive study with a Cross-Sectional approach which aims to describe the lung function of woodworkers in Petulu Gianyar Village. The sample in this study was taken using the simple random sampling method. The number of samples in this study consisted of 31 respondents. Primary data collection using a questionnaire and measuring lung function using spirometry.Results: The results of this study indicate that the respondents were 16 men (51.61%) and 15 women (48.39%). Respondents aged over 30 years were 25 people (80.65%) and aged under 30 years as many as 6 people (19.35%). Respondents with underweight nutritional status 1 person (3.23%), normal 15 people (48.39%) and fat 15 people (48.39%). Respondents with a working period of more than 5 years were 25 people (80.65%) and tenure under 5 years was 6 people (19.35%). Respondents who have smoking habits as many as 12 people (38.71%) and do not have smoking habits as many as 19 people (61.29%). Respondents who did not use personal protective equipment were 6 people (19.35%) and respondents who used personal protective equipment were 25 people (80.65%). The results of lung function measurements found that respondents who experienced restrictive pulmonary function disorders were 18 people (58.06%) and respondents with normal pulmonary function were 13 people (41.94%).Conclusion: Based on the results of the study showed that as many as 18 people (58.06%) wood craftsmen in Petulu Gianyar Village experienced restrictive lung function disorders.